1980
DOI: 10.1126/science.208.4447.1000
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Ocean Sector to the United States Economy

Abstract: The national income accounts have been reorganized to estimate the contribution to the gross national product of the ocean sector and its various subsectors for the year 1972. The new account is the first within the national income accounts to be organized along geographic, rather than productive, sectors. If properly updated and disseminated, this new account will give government and business interests a solid and consistent data base to measure, and choose among, the alternative uses of the oceans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…The categorization of these land uses as marine-related is based on our observations and is similar to the categories used by Pontecorvo et al (1980). 7 'Fishing' referred to parcels that provided docking and tie-up facilities for non-recreational, commercial fishing vessels.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The categorization of these land uses as marine-related is based on our observations and is similar to the categories used by Pontecorvo et al (1980). 7 'Fishing' referred to parcels that provided docking and tie-up facilities for non-recreational, commercial fishing vessels.…”
Section: Data Collectionmentioning
confidence: 99%
“…Pontecorvo et al (1980) used supply-side and demand-side criteria to categorize ocean and non-ocean businesses. These include extractive and spatial criteria in which the primary activity of the establishment involves extraction of living or inanimate objects from the ocean, utilizes ocean water as a significant element in the production process, or involves some manner of transportation of passengers, cargo, natural resources, or electrical impulses upon or below the ocean surface.…”
mentioning
confidence: 99%
“…We determined the land uses of interest to be: fishing, processing, repair, transport, and boating (see Table 3). The categorization of these land uses as marine-related was based on our observations and was similar to the categories used by Pontecorvo et al (1980). 4 In New Bedford in 2006, 59% of the study area consisted of parcels dedicated to at least one of these activities.…”
Section: Spatial Land Use Datamentioning
confidence: 99%
“…However, until recently, economic indicators were not commonly used to measure geographic slices of the economy such as oceans, forests, or fields. Estimating the value of an "ocean economy" was unheard of until the 1970s (Pontecorvo et al, 1980) and even then research only reported a snapshot in time, not the time series necessary to understand trends. Currently numerous nations including the USA, the UK, France, and Canada keep ocean accounts that help them to better understand the status, nature, and value of that ocean economy, and to identify the trends that underlie projections and forecasts.…”
Section: Indicatorsmentioning
confidence: 99%